IMPACT OF CONSUMER DECISION MAKING: THE ROLE OF LOCATION, PRICE, AND PRODUCT COMPLETENESS IN A RURAL RETAIL CONTEXT - Khotijah, Siti Nur; Mutammimah, Mamik; Farid, Muhammad; Hidayatullah, Indra (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Indonesia is a developing country with great potential in business and trade, including the retail sector such as department stores (toserba). The success of retail businesses is influenced by several factors, including location, price, and product availability. This study aims to analyze the influence of these three factors on consumer purchasing decisions at Toserba Al-Ikhwan Banyuputih Kidul (Bakid). The approach used is quantitative, with location, price, and product availability as independent variables, and purchasing decisions as the dependent variable. Because the population size is unknown, the sampling technique used is quota sampling with the Lemeshow formula. Data were obtained through observation and questionnaires. The results of the study indicate that all three variables have a significant effect on purchasing decisions, both simultaneously and partially. Store location has a t-value of 2.071 (significance 0.041), product availability 2.294 (significance 0.024), and product price is the most dominant factor with a t-value of 10.129 (significance 0.001). Simultaneously, the three variables had a significant influence with a calculated F value of 113.272 and a significance level of 0.000. These findings can serve as a reference for convenience store managers in developing effective marketing strategies to increase consumer satisfaction and loyalty.